Legal Responsibility of Insurance Companies for the Denial of COVID-19 Patient Claims: A Case Study of PT Asuransi Allianz Life Indonesia - Lidya Thalia; Zahra Balqis Ananda; Rivky Abdillah Putra; Abdul Latif; Ahmad Yani Anshori (ISNU Nine-Star Multidisciplinary Journal, 2025)
In this article, we examine the legal responsibility of insurance companies for the denial of COVID-19 patient claims: A case study of PT Asuransi Allianz Life Indonesia. Aims to find out how the company's responsibility is to customers, how to protect consumers, and how insurance customers respond to the rejection of COVID-19 claims This research uses a qualitative method, namely by using a field study and analytical descriptive approach. The results of this study have shown that PT Asuransi Allianz Life Indonesia, in certain cases, has not fully fulfilled its legal responsibilities both from a contractual perspective and within the framework of consumer protection. This refusal creates a conflict because in contract law, an agreement must be executed based on the principles of good faith and transparency of information. Many customers expressed disappointment with Allianz's perceived impartiality and seemed to be looking for excuses to reject claims.